Battle of the scores: validating the AIR, Alvarado and Tzanakis scores in acute appendicitis - Srivastava, Vaibhav; Tripathi, Piyush S.; Sharma, Harshit; Shukla, Nishant (International Surgery Journal, 2025)
Background: Acute appendicitis is one of the most common surgical emergencies, yet its diagnosis remains challenging. Scoring systems such as the Modified Alvarado Score (MAS), Appendicitis Inflammatory Response (AIR) score and Tzanakis score have been proposed to improve diagnostic accuracy. Methods: A prospective observational study was conducted on 92 patients presenting with suspected acute appendicitis at Moti Lal Nehru Medical College, Prayagraj after obtaining approval from Institutional Ethics Committee. Each patient was assessed using MAS, AIR and Tzanakis scores. Final diagnosis was confirmed by histopathological examination. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated for each scoring system. Results: The Tzanakis score showed the highest diagnostic performance (sensitivity 95.12%, specificity 91.34%, PPV 96.42%, NPV 89.58%), followed by AIR score (sensitivity 93.25%, specificity 88.17%, PPV 94.78%, NPV 85.21%). MAS demonstrated comparatively lower accuracy (sensitivity 83.0%, specificity 71.4%). Patients evaluated with Tzanakis score also had the highest proportion of timely appendicectomies and the lowest rate of unnecessary surgeries. Conclusions: The Tzanakis score emerged as the most reliable tool for diagnosing acute appendicitis due to its integration of clinical, laboratory and ultrasonographic data. The AIR score also showed high diagnostic utility, especially in settings lacking immediate imaging. MAS, while useful as an initial assessment tool, demonstrated limited diagnostic precision.